The decline of a superpower - Faucher, Steven Harlow (1994)
The predictions for America’s future are a little shaky, but far from gloomy.Although the USA will probably never regain the leadership it had following World WarII, possibly a tripartite role with Japan and West Germany may be feasible. However, theAmerican economy does appear to be making a comeback. JEL Classification: F50; F54.